2021
DOI: 10.1111/ajt.16336
|View full text |Cite
|
Sign up to set email alerts
|

Validity and utility of urinary CXCL10/Cr immune monitoring in pediatric kidney transplant recipients

Abstract: Individualized posttransplant immunosuppression is hampered by suboptimal monitoring strategies. To validate the utility of urinary CXCL10/Cr immune monitoring in children, we conducted a multicenter prospective observational study in children <21 years with serial and biopsy‐associated urine samples (n = 97). Biopsies (n = 240) were categorized as normal (NOR), rejection (>i1t1; REJ), indeterminate (IND), BKV infection, and leukocyturia (LEU). An independent pediatric cohort of 180 urines was used for externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(74 citation statements)
references
References 54 publications
3
71
0
Order By: Relevance
“…While 60%–70% of clinicians rely on graft functional markers to define BPAR resolution, 11 , 12 serum creatinine is very insensitive with only an AUC 0.59 for detecting BPAR. 13 There is a dearth of evidence evaluating histologic persistence of BPAR after anti‐rejection therapy for TCMR. Indeed a systematic review of BPAR treatment from 1997 to 2015 identified only five studies that examined the response to anti‐rejection therapy and these studies used graft function, not histology.…”
Section: Introductionmentioning
confidence: 99%
“…While 60%–70% of clinicians rely on graft functional markers to define BPAR resolution, 11 , 12 serum creatinine is very insensitive with only an AUC 0.59 for detecting BPAR. 13 There is a dearth of evidence evaluating histologic persistence of BPAR after anti‐rejection therapy for TCMR. Indeed a systematic review of BPAR treatment from 1997 to 2015 identified only five studies that examined the response to anti‐rejection therapy and these studies used graft function, not histology.…”
Section: Introductionmentioning
confidence: 99%
“…In the search for biomarkers and therapeutic targets for acute rejection, several research groups have suggested to study cytokines, as they play a crucial role in the pathophysiology of rejection (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). However, studies focusing on only one or few molecules miss the complexity of the interactions and the interplay between the full landscape of cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…36 Urinary biomarkers including CXCL10 immune monitoring in pediatric transplant recipients using the urine CXCL10/Cr levels defined the risk of rejection, immune quiescence and decline in allograft function and are being studied for real-time clinical monitoring. 37 Similarly, a urinary composite score based on the measurements of six urinary DNA, protein, and metabolic markers demonstrated clinical utility for predicting acute rejection before the rise in serum creatinine levels. 38 Ultimately, it will likely be a combination of dd-cfDNA and other biomarkers which will be able to reliably diagnose and determine response to treatment for all types of rejection.…”
Section: Discussionmentioning
confidence: 99%